1994
DOI: 10.1016/0014-5793(94)01058-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in activation gating of IsK potassium currents brought about by mutations in the transmembrane sequence

Abstract: Expression of the rat kidney IsK protein in Xenopus oocytes produces slowly-activating potassium channel currents. We have investigated the relationship between structure and function of the single putative membrane-spanning domain using site-directed mutagenesis. Six mutants were constructed in which consecutive individual amino acids (53 to 58) of the transmembrane region were substituted by cysteine. Expression of four of these mutants in Xenopus oocytes resulted in currents which were similar to wild-type.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…The demonstration of an α-helical conformation for the peptide in phospholipid membranes is in good agreement with a proposed model based on site-directed mutagenesis studies. Point mutations reveal the importance in activation gating of every third amino acid residue in the transmembrane region which, in an α-helical conformation, would align these amino acid residues along one face of the helix, forming one side of the pore as part of a multimer [6]. An α-helical conformation of the 28-residue transmembrane spanning region of minK would traverse the membrane once, placing the N-terminus on the extracellular side and the C-terminus on the intracellular side of the membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The demonstration of an α-helical conformation for the peptide in phospholipid membranes is in good agreement with a proposed model based on site-directed mutagenesis studies. Point mutations reveal the importance in activation gating of every third amino acid residue in the transmembrane region which, in an α-helical conformation, would align these amino acid residues along one face of the helix, forming one side of the pore as part of a multimer [6]. An α-helical conformation of the 28-residue transmembrane spanning region of minK would traverse the membrane once, placing the N-terminus on the extracellular side and the C-terminus on the intracellular side of the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that the N-and Cterminal domains serve to regulate the minK channel [5]. Point mutations in the putative transmembrane domain of minK resulting in altered gating and ion selectivity strongly suggest that minK forms an integral part of the channel [6].…”
Section: Introductionmentioning
confidence: 99%
“…24 Nuclear magnetic resonance spectroscopy of a peptide corresponding to KCNE1's transmembrane domain suggests that this region may adopt an ␣-helical structure when embedded in the membrane lipid bilayer. 25 Importantly, positions in the KCNE1 transmembrane domain where mutations can impact on KCNE1 modulation of KCNQ1 pore conductance and/or gating kinetics are found to cluster to one face of the putative KCNE1 ␣-helix, 24,26,27 suggesting that this may be part of the "KCNQ1-interacting" surface. 25 It has been suggested that the side chain at position 331 on KCNQ1's S6 (inner helix of the pore domain) may be in close proximity to side chains at positions 54 and 55 on KCNE1's transmembrane domain, 28 providing a further constraint on how KCNE1's transmembrane domain can interact with KCNQ1's pore domain.…”
Section: Implications For the Structural Basis Of Kcnq1 Modulation Bymentioning
confidence: 98%
“…The self-assembly of IsK in vivo is such that glycines 53 and 56 are in contact with the lipid chains in the cell membrane, while phenylalanines 54, 55, 57, and 58 are not (58). From the model of the helical K27 structure, it becomes clear that the corresponding glycines 12 and 15 of K27 are indeed on the same side of the helix, while the corresponding phenylalanines 13, 14, 16, and 17 are on its opposite side, in keeping with the functional results obtained with IsK.…”
Section: Implications Of Thementioning
confidence: 99%